Uptake of and Motivational Responses to Mental Health-Promoting Practices: Comparing Relaxation and Mindfulness Interventions - Beattie, Marguerite M.; Hankonen, Nelli E.; Konttinen, Hanna M.; Volanen, Salla-Maarit (Frontiers in Psychology, 2022)
Background: Comparative analyses of alternative interventions within the same trial enable acceptability and fidelity of each to be investigated more critically. In addition, whereas so far studies have focused on efficacy evaluations, more understanding is needed on motivational factors influencing the uptake of mental health-promoting practices rather than solely their effects. Purpose: This study investigates whether the motivational responses to a mindfulness intervention are different from a relaxation intervention. We compare social cognitions outlined by the Reasoned Action Approach and their roles in practice uptake, self-reported reasons for non-practice, and experienced benefits. Methods: In a cluster-randomized trial (N=3134), 12-15-year-old participants were given a 9-week intervention and followed up to 52 weeks. Main statistical analyses included t-tests, mixed ANOVAs, path models, and chi-square tests. Results: Social cognitions in the mindfulness arm were slightly more positive immediately post-intervention, but recipients mostly responded similarly to the two interventions in the longer term. While attitudes, norms, intention, and self-efficacy were relatively high post-intervention, most of them slightly decreased by 26 weeks. Main reasons for non-practice in both arms included not finding the exercises helpful, no felt need, boringness of exercises and forgetting. The most common benefits experienced by practicing respondents were stress management and concentration ability. Better sleep was a more frequently reported benefit in the relaxation arm, but no other major differences emerged. Conclusions: This study offers an example of comparing motivational responses to experimental and active control arm interventions, a potentially helpful approach in improving intervention adherence.